IMPROVING PHYSICS TEACHING METHODS IN GENERAL SECONDARY SCHOOLS BASED ON THE RISA INTERNATIONAL ASSESSMENT PROGRAM - Absalyamova Ilmira Ildarovna; Abdullayeva Shoira Isajanovna; Ochilova Ozoda Odilovna; Xalilova Nozliya Samadovna (Bright Mind Publishing, 2025)
This article explores strategies to enhance physics teaching in general secondary schools, drawing on insights from the Research on Improving Systems of Education (RISE) international assessment program. It analyzes global educational challenges, particularly in developing countries, and proposes evidence-based teaching methods to improve student learning outcomes in physics. The article reviews literature on physics education, discusses innovative teaching styles, presents findings from RISE-inspired interventions, and offers practical suggestions for educators and policymakers to address the learning crisis in physics.
Keywords: Physics education, secondary schools, RISE program, teaching methods, inquiry-based learning, student engagement, educational reform, learning outcomes.